Analysis of Students' Concept Understanding Ability Through E-Modules on Linear Program Materials - Fransiska Dwi Lestari; Ali Syahbana; Allen Marga Retta (Department of Mathematics Education University of Muhammadiyah Malang, 2022)
One of the mathematical abilities that students must master in order to learn mathematics is the ability to understand concepts, since it can affect the quality of learning and academic accomplishment of students. If the student's idea understanding is good, he or she will be able to solve the problem using the procedure. As a result, the goal of this study is to determine and describe students' grasp of mathematical ideas in linear programming material. This study's instrument is a set of learning outcomes test questions that refer to indications of concept comprehension. A qualitative research design is used in this study. Data reduction, data presentation, and generating conclusions were used to examine the data in this study. According to the findings, 33 students were able to meet the indicators of the ability to understand mathematical concepts by providing examples and non-examples, which received the highest percentage value, followed by indicators presenting concepts in various forms of mathematical representation, which received the second highest percentage value.